Commensal discovery of four fast radio bursts during Parkes Pulsar Timing Array observations. Issue 1 (28th June 2019) - Osłowski, S; Shannon, R M; Ravi, V; Kaczmarek, J F; Zhang, S; Hobbs, G; Bailes, M; Russell, C J; van Straten, W; James, C W; Jameson, A; Mahony, E K; et al.
ABSTRACT: The Parkes Pulsar Timing Array (PPTA) project monitors two dozen millisecond pulsars (MSPs) in order to undertake a variety of fundamental physics experiments using the Parkes 64-m radio telescope. Since 2017 June, we have been undertaking commensal searches for fast radio bursts (FRBs) during the MSP observations. Here, we report the discovery of four FRBs (171209, 180309, 180311, and 180714). The detected events include an FRB with the highest signal-to-noise ratio ever detected at the Parkes Observatory, which exhibits unusual spectral properties. All four FRBs are highly polarized. We discuss the future of commensal searches for FRBs at Parkes.